Slowing Cardiovascular Disease Progression in African‐American Patients: Diabetes Management - Gavin, James R. (J Clin Hypertens (Greenwich), 2007)
The prevalence of type 2 diabetes has grown to epidemic proportions in the United States and is disproportionately higher in certain ethnic groups. African Americans, Hispanic Americans, Native Americans, and Asian Americans have an approximately two‐fold higher rate of type 2 diabetes than whites. The increased prevalence of type 2 diabetes mirrors the growing rates of overweight and obese persons in the United States. While the highest rate of diabetes occurs at age 60 years and older, the fastest growing segment of the population with type 2 diabetes is younger than age 39 years. Because most diabetes‐related deaths are due to cardiovascular disease, an aggressive management strategy for type 2 diabetes must address both coronary heart disease risk factor reduction and glycemic control. Both the microvascular and macrovascular complications of type 2 diabetes can be prevented or slowed with aggressive therapy. Glycemic dysfunction can be moderated by aggressive combination therapy that focuses on the pathophysiology of diabetes in an individual patient and combines two or three oral agents, such as an insulin sensitizer with an insulin secretagogue or two insulin sensitizers with different loci of action. The goal of glycemic control is reduction of glycated hemoglobin to <7%. An appropriate management strategy should not be limited to lowering blood glucose levels alone but must also address obesity, hypertension, dyslipidemia, atherosclerosis, and the increased tendency for clotting in persons with type 2 diabetes. Treatment to reduce blood pressure to <130/80 mm Hg is recommended; to accomplish this, multiple antihypertensive agents are usually necessary. The goals for correction of dyslipidemia are to reduce low‐density‐lipoprotein cholesterol levels to <100 mg/dL, increase high‐density‐lipoprotein cholesterol levels to >40 mg/dL for men and >50 mg/dL for women, and decrease triglyceride levels to <150 mg/dL. Optimal therapy for persons with diabetes should include diet and exercise with medical nutrition therapy, lowering glycated hemoglobin with intensive glycemic control, and correcting high blood pressure and dyslipidemia with early, intensive, multidrug pharmacologic therapy.